Loading Rate and Bedding Plane Coupled Effect Study on Coal Failure under Uniaxial Compression: Acoustic Emissions and Energy Dissipation Analysis. (19th July 2022) - Zhou, Jinlong; Zhao, Yixin; Paneiro, Gustavo; Liu, Wengang; Wang, Xiaoliang; Wang, Hao; Gao, Yirui; Han, Chujian; Zhang, Xiufeng
Abstract : The mechanical behavior of coal is significantly influenced by the loading rate and bedding plane. In this paper, the uniaxial compression tests at different loading rates were conducted on coal specimens with vertical bedding (CSVB) and coal specimens with parallel bedding (CSPB), which were prepared by the coal with bursting liability from the Ordos deep mining areas, China. The results show that the uniaxial compressive strengths of CSVB and CSPB are positively correlated with the loading rate. The peak values of acoustic emission (AE) counts and accumulated absolute AE energy of CSVB and CSPB increase with the loading rate, and the AE parameters of CSVB are larger than those of CSPB. The variation rules of input energy density and elastic energy density are similar for CSVB and CSPB, but the variation rules of dissipated energy density in stage IV are different. As the axial load increases, the energy storage rate and energy dissipation rate of both coal specimen types increase and decrease, respectively. The bedding planes of coal and the loading conditions in the field should be fully considered when identifying the bursting liability of coal and forecasting coal burst. This study can provide a reference for coal burst warning and prevention under similar geological conditions in Ordos deep mining areas.